1994
DOI: 10.1007/bf01739028
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of ampicillin and sulbactam into human costal cartilage

Abstract: The question of whether ampicillin and sulbactam are able to penetrate sufficiently into costal cartilage tissue was investigated in 21 children undergoing surgery for funnel chest malformations. The concentrations of both compounds were determined in the core and mantle pieces of samples taken 45 min or 120 min after infusion of ampicillin/sulbactam (33.3/16.7 mg/kg bodyweight) preoperatively for antibiotic prophylaxis. Ampicillin was determined by bioassay and sulbactam was determined by gas-chromatography/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Likewise, ampicillin/sulbactam has been shown to penetrate cartilage sufficiently to exceed the minimum inhibitory concentrations of important bacterial pathogens (namely Staphylococcus spp) involved in postoperative wound infections and has been found to be a wellsuited agent for perioperative prophylaxis in thoracic surgery. 11 Additionally, in this case the infection was initially suspected to be caused by Staphylococcus spp, which always raises concern for methicillinresistant S. aureus, for which our hospital's antibiogram demonstrates excellent coverage with Unasyn.…”
Section: Discussionmentioning
confidence: 96%
“…Likewise, ampicillin/sulbactam has been shown to penetrate cartilage sufficiently to exceed the minimum inhibitory concentrations of important bacterial pathogens (namely Staphylococcus spp) involved in postoperative wound infections and has been found to be a wellsuited agent for perioperative prophylaxis in thoracic surgery. 11 Additionally, in this case the infection was initially suspected to be caused by Staphylococcus spp, which always raises concern for methicillinresistant S. aureus, for which our hospital's antibiogram demonstrates excellent coverage with Unasyn.…”
Section: Discussionmentioning
confidence: 96%
“…Conventional sulbactam dosing (administered as 2/1 g of ampicillin/sulbactam every 6 h) has been suggested to be appropriate for achieving adequate penetration across the blood-brain barrier, depending on the degree of meningeal inflammation and the susceptibility of the organism [40,42]. Similarly, favourable penetration resulting in therapeutic exposure has been shown for other sites including costal cartilage, middle ear fluid, peritoneal fluid, intestinal mucosa, prostatic and appendicular tissue, sputum and peritonsillar abscess pus [43,44]. For infections involving the lower respiratory system, particularly VAP, achieving effective epithelial lining fluid concentrations of antibiotics can be challenging for some therapies [45,46], although SAM appears to penetrate well [47,48].…”
Section: Distributionmentioning
confidence: 98%
“…23 Several studies have demonstrated that ampicillin/sulbactam achieves good penetration of relevant tissues in pediatric patients. Nahata et al 19 24 and middle-ear fluid. 25 A clinical study by Foulds et al 17 showed that sulbactam does not decrease and may actually increase the penetration of ampicillin into the CSF.…”
Section: Pharmacokineticsmentioning
confidence: 99%